Development of Mathematics Literacy Questions on Trigonometry - Aqillah, Hoirun Nisa; Kurniasi, Eka Rachma; Agustine, Putri Cahyani (S&Co Publishing, 2023)
The 2022 Education Report reveals that high school-equivalent students scored 50.74% in numeracy literacy, below the minimum competency. Emphasizing mathematical literacy is crucial, yet such problems are scarce in classrooms. The research aims to develop mathematical literacy questions. The trigonometry material was chosen for the reason that this material should enable literacy activities related to material concepts. Following the ADDIE (Analysis, Design, Implementation, and Evaluation) model, the study employs expert validation and student responses as instruments, involving 20 students in small and large-scale test phases. It yields four trigonometry essay questions for high school. The research results show that the Mathematical Literacy test developed has quite valid categories in terms of content, construct and language. The questions are declared reliable. All types of questions are difficult. Discrimination index of questions, 1 question in the average category, and 3 questions in the low category. The developed questions are in the difficult category because at the mathematical literacy level, the abilities that are developed are not at the level of low-level thinking. This research supports efforts to increase student competency in mathematical literacy at the high school level.